Alternative strategies for the synthesis of [11C]ER176 for PET imaging of neuroinflammation. (December 2021) - Mixdorf, Jason C.; Murali, Dhanabalan; Xin, Yangchun; DiFilippo, Alexandra H.; Aluicio-Sarduy, Eduardo; Barnhart, Todd E.; Engle, Jonathan W.; Ellison, Paul A.; Christian, Bradley T.
Abstract: [ 11 C]ER176 is a next generation PET radioligand for imaging 18 kDa translocator protein, a biomarker for neuroinflammation. The goal of this work was to investigate alternative strategies for the radiochemical synthesis, purification, and formulation of [ 11 C]ER176. An optimized tri-solvent high-performance liquid chromatography (HPLC) protocol is described to separate the hydro-de-chlorinated byproduct from [ 11 C]ER176. A newly implemented solid phase extraction work-up efficiently removed HPLC solvent while maintaining chemical purity and overall radiochemical yield and purity. This new HPLC purification and final formulation was completed within 40 min, providing 2.7 ± 0.5 GBq of [ 11 C]ER176 at end of synthesis with 1400 ± 300 GBq/μmol molar activity while meeting all specifications for radiopharmaceutical quality control tests for human research use. Highlights: New ternary isocratic semi-preparative HPLC providing improved resolution of [ 11 C]ER176 from non-radioactive impurity. Identification of non-radioactive impurity that elutes proximal to [ 11 C]ER176 and preliminary mechanistic investigation of its formation. Purification of [ 11 C]ER176 utilizing solid-phase extraction (SPE) for removal of semi-preparatory HPLC mobile phase. Production of [ 11 C]ER176 within 40 min, providing 2.7 ± 0.5 GBq at end of synthesis with 1400 ± 300 GBq/μmol molar activity.